Performance indicators for supply chain resilience: Review and conceptual framework - Chandra Shekhar Singh; Gunjan Soni; Gaurav Kumar Badhotiya (Journal of Industrial Engineering International, 2019)
In the current competitive and dynamic market, customer demands and interests are changing continuously, and hence, risk of disruption in the supply chain is also increasing. To be successful in this scenario, supply chain of a firm should be resilient. Most of the firms realize that with a specific end goal to develop a resilient supply chain, there is a need for assessment of performance. The purpose of this paper is to discuss supply chain resilience and identify indicators which can help in increasing the performance and making a supply chain resilient. Articles published on this issue were collected and classified to draw out some meaningful information. After classification and analyses of the collected literature, seventeen performance indicators for supply chain resilience are found. A supply chain resilience framework is developed using these indicators to assist the supply chain managers to examine and withstand the disruption.
Keywords: 650; Supply chain; Resilience; Performance indicators; Literature review; Framework